Faktor Yang Mempengaruhi Kepuasan Pengguna Jasa Transportasi Laut Kapal Fery MKP Dharma Kartika VIII Milik PT.Dharma Lautan Utama Cabang Palembang - Arsad, Tantawan; Syafriyansyah; Dina Mariana (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to identify the factors influencing passenger satisfaction on the KMP Dharma Kartika VIII Ferry operated by PT. Dharma Lautan Utama, Palembang Branch. A total of 100 respondents participated in the survey, the majority being male (65%) and aged between 17–25 years (40%). Data from the last three months indicate an increase in both passenger and vehicle numbers, emphasizing the vessel’s crucial role in transportation and distribution activities. The findings reveal that price perception received positive evaluations, with 62% of respondents strongly agreeing that the fare is affordable, and 50% expressing high satisfaction. Trust in the company’s performance, integrity, and brand image was also rated highly, with 33% of respondents being very satisfied and 40% satisfied. Service quality was assessed positively, with 46% of respondents stating they were very satisfied with the services provided. Validity and reliability tests confirmed the data’s feasibility for analysis. The coefficient of determination showed that price perception, trust, and service quality collectively influence customer loyalty by 82.6%. However, partially, only trust and service quality had a significant impact. Based on these findings, it is recommended that the company continue to improve service quality and strengthen customer trust to maintain loyalty.